It's getting Scot in here - Enoch, Suzanne (Enoch, Suzanne. Wild wicked Highlanders., 2019)
London socialite Amelia-Rose Baxter is nobody<U+2019>s fool. Her parents may want her to catch a title, but she will never change who she is for the promise of marriage. Her husband will be a man who can appreciate her sharp mind as well as her body. A sophisticated man who loves life in London. A man who considers her his equal<U+2015>and won<U+2019>t try to tame her wild heart... Rough, rugged Highlander Niall MacTaggert and his brothers know the rules: the eldest must marry or lose the ancestral estate, period. But Niall<U+2019>s eldest brother just isn<U+2019>t interested in the lady his mother selected. Is it because Amelia-Rose is just too. . . Free-spirited? Yes. Brazen? Aye. Surely Niall can find a way to soften up the whip-smart lass and make her the perfect match for his brother for the sake of the family. Instead it<U+2019>s Niall who tempts Amelia-Rose, despite her reservations about barbarian Highlanders. Niall finds the lass nigh irresistible as well, but he won<U+2019>t make the mistake his father did in marrying an Englishwoman who doesn<U+2019>t like the Highlands. Does he have what it takes to win her heart? There is only one way to find out...